Impacts of impaired mitochondrial dynamics in hearing loss: Potential therapeutic targets - Zou, Tianyuan; Ye, Bin; Chen, Kaili; Zhang, Andi; Guo, Dongye; Pan, Yi; Ding, Rui; Hu, Haixia; Sun, Xingmei; Xiang, Mingliang (Frontiers in Neuroscience, 2022)
Mitochondria are the powerhouse of the cells. Under physiological conditions, mitochondrial fission and fusion maintain a dynamic equilibrium in the cytoplasm, which is referred to as mitochondrial dynamics. As an important approach to regulating mitochondrial function and quantity, the role of mitochondrial dynamics has been demonstrated in the pathogenesis of various disease models, including brain damage, neurodegeneration, and stress. As the vital organ of the peripheral auditory system, the cochlea consumes a significant amount of energy, and the maintenance of mitochondrial homeostasis is essential for the cochlear auditory capacity. OPA1 functions as both a necessary gene regulating mitochondrial fusion and a pathogenic gene responsible for auditory neuropathy, suggesting that an imbalance in mitochondrial dynamics may play a critical role in hearing loss, but relevant studies are few. In this review, we summarize recent evidence regarding the role of mitochondrial dynamics in the pathogenesis of noise-induced hearing loss, drug-induced hearing loss, hereditary hearing loss, and age-related hearing loss. The impacts of impaired mitochondrial dynamics on hearing loss are discussed, and the potential of mitochondrial dynamics for the prevention and treatment of hearing loss is considered.